Matching ecological transition and food security in the cereal sector: The role of farmers' preferences on production contracts - Ciliberti, Stefano; Frascarelli, Angelo; Martino, Gaetano (Frontiers in Sustainable Food Systems, 2023)
Under an increasing demand from citizen and public institutions, agri-food supply chains are requested to comply with stringent environmental requirements. Moreover, new sources of uncertainty related to pandemic and geo-political turbulences put further pressures on economic agents, calling for proper and resilient governance mechanisms. Under the lens of the Neo Institutional Economics, we focus on production contracts and their clauses which, in turn, perform different functions and contribute to allocate property and decision rights, in the attempt to conciliate sustainability and food security. In this framework, contract design assumes a key importance. Thus, we analyze farmers’ preferences for different contractual clauses in the cereal sector. A choice experiment is carried out among durum wheat producers in Italy and econometric analyses assuming heterogeneous preferences are performed. Findings offer interesting indications for both stakeholders, revealing a strong farmers’ willingness to adhere production contracts in exchange for price stability and knowledge transfer offered by technical assistance services. However, producers are not available to limit their decisional autonomy in unilateral agreement with buyers and they reveal a certain indifference to costly production techniques aimed to improve environmental sustainability.